DNA methylation of imprinted genes in Mexican–American newborn children with prenatal phthalate exposure. (29th June 2018) - Tindula, Gwen; Murphy, Susan K; Grenier, Carole; Huang, Zhiqing; Huen, Karen; Escudero-Fung, Maria; Bradman, Asa; Eskenazi, Brenda; Hoyo, Cathrine; Holland, Nina
Aim: Imprinted genes exhibit expression in a parent-of-origin-dependent manner and are critical for child development. Recent limited evidence suggests that prenatal exposure to phthalates, ubiquitous endocrine disruptors, can affect their epigenetic dysregulation.Materials & methods: We quantified DNA methylation of nine imprinted gene differentially methylated regions by pyrosequencing in 296 cord blood DNA samples in a Mexican–American cohort. Fetal exposure was estimated by phthalate metabolite concentrations in maternal urine samples during pregnancy.Results: Several differentially methylated regions of imprinted genes were associated with high molecular weight phthalates. The most consistent, positive, and false discovery rate significant associations were observed for MEG3 .Conclusion: Phthalate exposure in utero may affect methylation status of imprinted genes in newborn children.